Investigation and Assessment the Level of SMES Leanness Using Fuzzy Dematel/Fuzzy AHP/Fuzzy Topsis Integrated Model - Al-Baldawi Zainab; Kassam Sawsan AllaEldin. H.; Al-Zubaidi Sabeeh A. (Management Systems in Production Engineering)
Small and Medium Enterprises (SMEs) have a crucial role in driving economic growth and innovation. In the modern business landscape characterized by uncertainty, the adoption of lean philosophy has gained prominence as a means to continuously improve SMEs’ operational efficiency and competitiveness. A fuzzy assessment model was proposed as comprehensive framework and guide for SMEs during their lean journey that utilizes the Fuzzy Analytic Hierarchy Process (Fuzzy AHP), Fuzzy Decision-Making Trial and Evaluation Laboratory (Fuzzy DEMATEL), and Fuzzy Technique for Order of Preference by Similarity to Ideal Solution (Fuzzy TOPSIS) to serve many objectives; identifying the most important and influence lean dimensions on SMEs leanness; assessing the level of adoption of lean philosophy in SMEs for five essential lean dimensions, namely management, process, supplier, customer, and employee; identifying the interrelationships among them; and identifying the driving dimensions for the improvement process to focus SMEs limited resources on it in improvement process due to its direct influence on the other lean dimensions. The proposed fuzzy model was applied in Iraqi medium-sized enterprise producing healthy water, juice, and soft drinks to identify the most important and influence lean dimension on enterprise leanness, identify the driving dimension of the improvement process, and assess the level of leanness of these five lean dimensions. The results showed that the management dimension has the highest level of importance and influence on SMEs’ leanness, equal to 41.31%, and is distinguished as a driving dimension that has a high influence on improving the driven dimensions of process and customer. Although the level of importance and influence of the process dimension is 19.96%, it is an effect dimension and is considered a driven dimension. Plotting the interrelationship among the five lean dimensions in the diagram shows management has an influence on all lean dimensions and, at the same time, has a mutual relationship with employees and customers. An employee has a mutual relationship with the process dimension. In addition, the results showed that enterprise has deficiency in adopting a lean philosophy, where its level of leanness equal 0.39.